2017
DOI: 10.3847/1538-4357/836/1/49
|View full text |Cite
|
Sign up to set email alerts
|

Pale Orange Dots: The Impact of Organic Haze on the Habitability and Detectability of Earthlike Exoplanets

Abstract: Hazes are common in known planet atmospheres, and geochemical evidence suggests early Earth occasionally supported an organic haze with significant environmental and spectral consequences. The UV spectrum of the parent star drives organic haze formation through methane photochemistry. We use a 1D photochemical-climate model to examine production of fractal organic haze on Archean Earthanalogs in the habitable zonesof several stellar types: the modern and early Sun, AD Leo (M3.5V), GJ 876 (M4V), Eridani (K2V), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
209
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(212 citation statements)
references
References 103 publications
2
209
1
Order By: Relevance
“…Recent ultraviolet (UV) studies have shown that even optically inactive M dwarfs (i.e., those displaying Hα spectra in absorption only) display evidence of chromospheric, transition region, and coronal activity France et al 2016) that may significantly affect heating and chemistry in the atmospheres of orbiting exoplanets (e.g., Segura et al 2003Segura et al , 2005Miguel et al 2015;Rugheimer et al 2015;Arney et al 2017). The Measurements lines that form in the stellar chromosphere and transition region, with a few lines originating in the corona.…”
Section: Uv and Ca Iikemission From M Dwarfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent ultraviolet (UV) studies have shown that even optically inactive M dwarfs (i.e., those displaying Hα spectra in absorption only) display evidence of chromospheric, transition region, and coronal activity France et al 2016) that may significantly affect heating and chemistry in the atmospheres of orbiting exoplanets (e.g., Segura et al 2003Segura et al , 2005Miguel et al 2015;Rugheimer et al 2015;Arney et al 2017). The Measurements lines that form in the stellar chromosphere and transition region, with a few lines originating in the corona.…”
Section: Uv and Ca Iikemission From M Dwarfsmentioning
confidence: 99%
“…Specifically, the spectral energy distributions (SEDs) of the host stars are essential, because molecular and atomic cross sections are strongly wavelength dependent. High-energy stellar flux heats upper planetary atmospheres and initiates photochemistry (e.g., Lammer et al 2007;Miguel et al 2015;Rugheimer et al 2015;Arney et al 2017). UVdriven photochemistry can produce and destroy potential biosignatures (O 2 , O 3 , and CH 4 ) and habitability indicators (H 2 O and CO 2 ) in exoplanet atmospheres (Hu et al 2012;Domagal-Goldman et al 2014;Tian et al 2014;Wordsworth & Pierrehumbert 2014;Gao et al 2015;Harman et al 2015;Luger & Barnes 2015).…”
Section: Uv and Ca Iikemission From M Dwarfsmentioning
confidence: 99%
“…Laboratory optical properties of oxidized organic aerosols are needed to refine models of the Archean Earth but also of exoplanet atmospheres. Although CO 2 is considered a minor carrier of carbon in exoplanetary atmospheres (Heng & Lyons 2016), its presence could greatly affect the formation and optical properties of photochemical hazes in Earth-like exoplanets (Arney et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In both cases the data quality is sufficient to identify molecular absorptions that enable to ambiguously discriminate a mature earth from and archean earth. 7,8 Top Right: The bandpasses in each channel of the LUVOIR coronagraph instrument defined in this manuscript are overlayed to the spectrum. UV, Optical and IR channels can operate in parallel, however the bandpasses in each channel can only be operated sequentially.…”
Section: Overview Of the Instrumentmentioning
confidence: 99%
“…Fig. 3 shows a simulated spectrum of a mature earth, along with an 2 Gyrs old Archean earth, generated with the LUVOIR STDT online exoplanet spectrum simulation tool * , using the underlying models by Arney et al 7 and Robinson.…”
mentioning
confidence: 99%